Neemazal ® as a possible alternative control tool for malaria and African trypanosomiasis?. Issue 1 (December 2016) - Yerbanga, R.; Rayaisse, Jean-Baptiste; Vantaux, Amélie; Salou, Ernest; Mouline, Karine; Hien, François; Habluetzel, Annette; Dabiré, Roch; Ouédraogo, Jean; Solano, Philippe; Lefèvre, Thierry
Abstract Background Research efforts to identify possible alternative control tools for malaria and African trypanosomiasis are needed. One promising approach relies on the use of traditional plant remedies with insecticidal activities. Methods In this study, we assessed the effect of blood treated with different doses of NeemAzal ® (NA, neem seed extract) on mosquitoes (Anopheles coluzzii ) and tsetse flies (Glossina palpalis gambiensis ) (i) avidity to feed on the treated blood, (ii) longevity, and (iii) behavioural responses to human and calf odours in dual-choice tests. We also gauged NeemAzal ® toxicity in mice. Results InAn. coluzzii, the ingestion of NA in bloodmeals offered by membrane feeding resulted in (i) primary antifeedancy; (ii) decreased longevity; and (iii) reduced response to host odours. InG. palpalis gambiensis, NA caused (i) a knock-down effect; (ii) decreased or increased longevity depending on the dose; and (iii) reduced response to host stimuli. In both cases, NA did not affect the anthropophilic rate of activated insects. Overall, the most significant effects were observed with NA treated bloodmeals at a dose of 2000 μg/ml for mosquitoes and 50 μg/ml for tsetse flies. Although no mortality in mice was observed after 14 days of follow-up at oral doses of 3.8, 5.6, 8.4 and 12.7 g/kg, behavioural alterations were noticed at doses above 8 g/kg. Conclusion This study revealed promising activity of NA onA. coluzzii andG. palpalis gambiensis but additional research is needed to assess field efficacy of neem products to be possibly integrated in vector control programmes.